Activation Energy and Couple Stresses Effect on MHD Peristaltic Transport of Jeffery Nanofluid between two Inclined Coaxial Tubes through a Non-Darcy Porous Medium - Abuiyada, Alaa J.; Eldabe, Nabil T.; Abou-zeid, Mohamed Y.; Shaboury, Sami M. El (Journal of Applied Nonlinear Dynamics, 2026)
The main purpose of this study is to investigate the influence of the chemical reaction and activation energy on peristaltic flow of MHD Jeffery nanofluid through a non-Darcy porous medium in the gap between two coaxial tubes inclined at an angle $α $. Couple stresses, radiation, heat generation/absorption, magnetic field, viscous dissipation, and thermal diffusion and diffusion thermo effects are taken into account. The long wavelength and low Reynolds number approximations are used to simplify the non-linear equations governing the flow. Then, a semi-analytical method called the homotopy perturbation method (HPM) is employed to solve the non-linear equations. Graphs for velocity, temperature, and nanoparticle concentration distributions are plotted. Graphical representations of skin friction coefficient, heat transfer coefficient, Nusselt number, and Sherwood number are sketched. Physical explanations for the results are provided. Findings revealed that the increase of the ratio of relaxation to retardation times of Jeffery nanofluid ${ {λ }}_ {1}$ and the couple stress coefficient ${η }'$ decreases the velocity profile, while the couple stress parameter ${γ }_1$ increases it. Also, the velocity has a dual behavior under the infuence of Darcy number $Da$ and Hartman number $M$. Moreover, the temperature decreases with an increase of the radiation parameter $R$, but an opposite reaction observes by increasing Hartman number $M$ and the thermophoresis parameter $Nt$. Furthermore, a reduction in the nanoparticle concentration profile occurs by increasing $ {ξ } $, ${ρ }_1$, and $ E$. The motion of gastric juice when an endoscope is inserted through a small intestine is a famous example that describes the model of this study.